The remarkable durability of Thirlwall’s Law - Setterfield, Mark (PSL Quarterly Review, 2011)
This paper contemplates the robustness of Thirlwall’s Law, a parsimonious expression that relates long run equilibrium growth in any one region to the product of world income growth and the ratio of the income elasticities of demand for exports and imports. Various extensions of the balance-of-payments-constrained growth model from which Thirlwall’s Law is derived are contemplated. In each case, Thirlwall’s Law is shown to reassert itself as a good approximation of the equilibrium growth rate. It is hypothesized that this robustness helps explain the widespread empirical success of Thirlwall’s Law. JEL Codes: O41, E12